Analisis Penyelenggaraan Pendidikan Inklusi Di Sekolah Dasar Kabupaten Lomok Tengah - Baiq Sriwulan Suantari; Endang Poerwanti; Ichsan Anshory (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to find out: 1) the conduct of inclusive education at elementary school level in Central Lombok regency, 2) the management of inclusive education at elementary school level of Central Lombok regency, 3) obstacle and effort conducted by schools that administer the inclusive education. This study is a descriptive qualitative study which applied qualitative method. Its sample was inclusive schools that are located in the rural area as well as downtown and the district capital of Central Lombok regency. The data collection technique was my interview with the Head of Education Board, Local Government of Central Lombok regency, observation related to inclusive education conduct in Central Lombok regency and in the form of photos to support the analysis result. The data analysis technique used the data reduction technique, data presentation, and verification. The result of the study showed that 1) inclusive education implementation in the learning process was done in classical form, there was no service provided by the school toward the children with a special need. The three schools which were taken as a sample of the study were not ready to establish inclusive education due to lack of understanding from the teachers’ side on inclusive education itself. 2) the uneven management system in terms of curriculum implementation, schools A and B applied KTSP while school C used K13 by government regulation. 3) the obstacles faced by the teachers were the lack of understanding from the teachers’ side, the unavailability of expert staff for the special needs, the lack of facility and utility, lack of training provided by the institution whose school administers the inclusive education. The effort should be done by teachers from respective schools is to proceed with the learning process for their students at their best, proceed with the inclusive education program in their respective schools.Keywords: Education, Inclusive, Elementary school Abstrak: Tujuan penelitian ini yaitu mengetahui: 1) Pelaksanaan pendidikan inklusi di sekolah dasar Kabupaten Lombok Tengah; 2) Manajemen pendidikan inklusi disekolah dasar Kabupaten Lombok Tengah; 3) Kendala dan upaya dan yang di alami sekolah dasar penyelenggara pendidikan inklusi. Desain yang digunakan dalam penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kualitatif deskriptif, dengan sample penelitian yaitu sekolah inklusi yang terletak di Daerah pelosok, di tengah-tengah Kota, dan terletak di Kota Kabupaten Lombok Tengah. Teknik pengumpulan data yaitu wawancara dengan Dinas Pendidikan, Pemerintah Daerah Kabupaten Lombok Tengan, observasi terkait pelaksanaan Pendidikan Inklusi di Kabupaten Lombok Tengah dan Dokumentasi yang berupa foto-foto untuk memperkuat hasil analisis. Teknik Analisis data dalam penelitian ini menggunakan teknik reduksi data, penyajian data dantahap Verifikasi. Hasil penelitian menunjukkan bahwa: 1) pelaksanaan pendidikan inklusi dalam proses pembelajaran dilakukan secara klasikal, belum terlihat pelayanan yang diberikan sekolah terhadap anak berkebutuhan khusus. Ketiga sekolah yang menjadi sample dalam penelitian ini tidak siap untuk menyelenggarakan pendidikan inklusi karena pemahaman guru terhadap konsep dari inklusi itu sendiri yang masihkurang. 2) manajemen sekolah dalam kurikulum masih menggunakan KTSP untuksekolah A dan B, sedangkan untuk sekolah C menggunakan kurikulum K13 sesuai ketetapan pemerintah. 3) kendala yang dihadapi guru berupapemahaman guru yang kurang, tidaktersedianya guru pembimbingkhusus, saranadanprasarana, pelatihan yang kurang yang disediakanolehlembagauntuk guru yang sekolahnya menyelenggarakan pendidikan inklusi. Upaya yang dilakukan oleh sekolah yaitu melaksanakan pembelajaran sebaik mungkin untuk para siswa, menlajutkan pendidikan inklusi di sekolah masing-masingKata kunci: Pendidikan, Inklusi, Sekolah dasar